ПОНЯТТЯ ФІНАНСОВОЇ СИСТЕМИ УКРАЇНИ ЯК ОБ'ЄКТА УПРАВЛІННЯ - КОБЗЄВА, Тетяна Анатоліївна (SUPREMANCE OF LAW, 2016)
The article, based on an analysis of theoretical approaches of domestic and foreign scientists, the essence of such concepts as “Finance”, “system” and “financial system”. It is proved that the financial system of Ukraine as an object of management, subject to the will of the ruling regulator and performs his decision, provided that the content and nature of the general legal category of “system”. Emphasized that the effective functioning of the financial system depends on organization management.
Keywords: finance system; the financial system of Ukraine; facility management; administrative and legal regulation.